The Effects of Economic News on Commodity Prices : Is Gold Just Another Commodity? - Roache, Shaun (IMF Working Papers; Working Paper ;, 2009)
The paper uses an event study methodology to investigate which and how macroeconomic announcements affect commodity prices. Results show that gold is unique among commodities, with prices reacting to specific scheduled announcements in the United States and the Euro area (such as indicators of activity or interest rate decisions) in a manner consistent with gold's traditional role as a safe-haven and store of value. Other commodity prices, where such news is significant, exhibit pro-cyclical sensitivities and these have risen somewhat as commodities have become increasingly financialized. These results are important for those trading in the commodity markets on a frequent basis and long-term market participants that take their decisions based on information on price fundamentals, which are reflected in the release of macroeconomic announcements.